2012
DOI: 10.2147/ijgm.s28902
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in a patient with left ventricular noncompaction: a case report

Abstract: We describe a 73-year-old male patient with left ventricular noncompaction (LVNC) who was diagnosed with acute myocardial infarction (MI), three-vessel coronary artery disease, a fresh intraventricular thrombus, and mitral regurgitation. He was treated with full anticoagulant therapy, coronary artery bypass grafting, and mitral valve repair. This case adds to a small but growing literature showing association between LVNC and MI and/or coronary artery disease. We suggest that patients with LVNC could be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first case of LVNC associated with anomalous coronary artery origin and STEMI reported in the literature. Seven cases of acute myocardial infarction (AMI) have been reported in patients with LVNC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], five of them were anterior STEMI in male patients aged between 45 and 63 years [ 14 , 16 , 17 , 18 , 19 ], and one was an AMI in a patient with three-vessels disease treated with coronary artery bypass graft (CABG) [ 20 ]. Panduranga et al reported a case of a patient with LVNC and STEMI, non-dyslipidemic, and hypothesized that a single gene responsible for both myocardial development and coronary endothelium could be involved in the pathogenesis of LVNC and at the same time predisposition to coronary atherosclerosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case of LVNC associated with anomalous coronary artery origin and STEMI reported in the literature. Seven cases of acute myocardial infarction (AMI) have been reported in patients with LVNC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], five of them were anterior STEMI in male patients aged between 45 and 63 years [ 14 , 16 , 17 , 18 , 19 ], and one was an AMI in a patient with three-vessels disease treated with coronary artery bypass graft (CABG) [ 20 ]. Panduranga et al reported a case of a patient with LVNC and STEMI, non-dyslipidemic, and hypothesized that a single gene responsible for both myocardial development and coronary endothelium could be involved in the pathogenesis of LVNC and at the same time predisposition to coronary atherosclerosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…ИМ был заподозрен клинически (уровень тропонина I в венозной крови 33,900 и >50,000 нг/мл в динамике) и подтвержден при патологоанатомическом исследовании. В литературе представлены описания сочетания НМЛЖ и подострого или острого ИМ 1 типа атерогенного генеза у пациентов старше 45 лет [41][42][43][44][45]. Güvenç TS, et al (2012) описывают клинический случай эмболического ИМ при интактных коронарных артериях по данным КАГ у 20-летнего мужчины с НМЛЖ [46].…”
Section: Discussionunclassified
“…A comprehensive echocardiographic study including M-mode, two-dimensional echocardiography, and Doppler echocardiographic measurements, was performed in all patients using an ultrasound system (Vivid 7; GE Healthcare, Horten, Norway) operated by an experienced cardiologist blinded to the multidetector CT findings. 15 – 18 The presence of mitral valve stenosis was defined as restriction of leaflet motion leading to a transmitral diastolic gradient. The severity of mitral stenosis was classified according to American College of Cardiology/American Heart Association guidelines.…”
Section: Methodsmentioning
confidence: 99%